MISSIONARY STRATEGIES AND INDIGENOUS RESPONSE: THE INTRODUCTION OF CHRISTIANITY TO THE BISENI CLAN - JOHN OLUWABUKUNMI OLUWAJANA; OLAITAN OYEDELA, OLAOBA (International Studies Journal)
This paper examines the indigenous responses to the introduction of Christianity to the Biseni Clan, focusing on the missionary strategies employed and the multifaceted reactions of the indigenous population. Drawing on historical accounts, oral traditions, and scholarly literature, the study explores how the missionaries' evangelization efforts intersected with pre-existing cultural and religious practices within the Biseni community. The indigenous responses to Christianity ranged from curiosity and intrigue to skepticism and resistance, reflecting the complex dynamics of cultural encounter and negotiation. Through an analysis of internal and external factors shaping indigenous responses, including social, political, and colonial influences, this paper sheds light on the nuanced and diverse ways in which the Biseni people engaged with the Christian message and its implications for their cultural identity.